Pengaruh Metode Tasmi’ dalam Meningkatkan Minat Menghafal Qur’an bagi Siswa di MTs Mualimin UNIVA Medan - Raini, Aljah (Darul Yasin Al Sys, 2024)
This study aims to explore the influence of the Tasmi’ method on increasing students' interest in memorizing the Qur'an. Utilizing a descriptive qualitative approach, the research collects data through interviews, observations, and documentation. Interviews were conducted with Qur'an teachers and students participating in the memorization program to gain in-depth insights into the implementation of the Tasmi’ method. Observations were made during the classroom learning process to see the direct application of the Tasmi’ method and the students' responses to it. Additionally, documentation includes records of students' memorization achievements and relevant learning reports. Data were analyzed through three stages: presentation, reduction, and verification. In the presentation stage, the data were organized systematically, while in the reduction stage, irrelevant data were filtered out, and significant data were retained. In the verification stage, the researcher drew conclusions based on the obtained results. The findings indicate that the Tasmi’ method significantly enhances students' interest in memorizing the Qur'an, with students feeling more motivated and engaged in the memorization process due to this approach. It is hoped that these findings will contribute to the development of more effective Qur'an teaching methods.